KEADILAN RESTORATIF (RESTORATIVE JUSTICE) DALAM PERKARA TINDAK PIDANA PENCURIAN (DI KEJAKSAAN NEGERI JAKARTA BARAT: Restorative Justice in Theft Crime Cases (at the West Jakarta District Attorney's Office) - Bustan, Josephine Kezia; Setiyono (AMICUS CURIAE, 2024)
Restorative justice is a new concept that may justify the suspension of criminal investigations throughout the criminal justice system. The West Jakarta District Attorney's Office investigated a theft case using this strategy. The problem studied was how the West Jakarta District Attorney's Office applied restorative justice to a theft case involving suspect Hendra Yohanes and how it was evaluated in a non-criminal case involving the same suspect. This descriptive research uses normative legal studies to show how restorative justice can resolve criminal cases. This research uses primary and secondary sources to obtain information. The West Jakarta District Attorney's Office abandoned the restorative justice prosecution of a theft case after going through procedural steps conducted by the facilitating prosecutor, according to the results of the research. The West Jakarta District Attorney's Office issued a Decree to Discontinue Prosecution to resolve Hendra Yohanes' theft case after reconciling with the victim, the suspect's apology, and a statement that he would not reoffend.